Impact of Lithuanian EU Integration on External Trade in Agricultural Products - Miškinis, Algirdas (Ekonomika, 2004)
The task of the study was to identify the impact of EU membership on Lithuanian trade in food products. The author has carried out an analysis of the inevitable and likely changes which will affect Lithuanian trade policy. terms of trade within the EU and the third countries, export and import volumes, and social consequences of these changes. The conclusions are based on a comparison of the existing Lithuanian and EU tariffs for key items of Lithuanian foodstuffs exports and imports.